Choice of Treatment Intensities by a Nonprofit Hospital Under Prospective Pricing - William P. Rogerson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
Under prospective pricing, payers for health care essentially use price regulation of hospitals as a way of indirectly regulating the provision of treatment intensity. This paper ppresents a theory of how a nonprofit hospital selects treatment intensities for its priducts given the payer's choice of prices and then determines how the payer should select prices in light of this theory. The main result is that, in quilibrium, the ration of price to marginal cost will vary across products inversely with the elasticity of demand with respect to treatment intensity. This means that, generally, the hospital will earn positive(negative) accounting profit on products with low(high) intensity elasticities of demand.
Keywords: 330